The denominations of the locals of Metropolitan Lima and Callao: gentilics y lexicography - Lovón Cueva, Marco Antonio (2019)
The gentilics are used to refer to the name given to the people from a particular region or country. In Peru, studies that focus on the denominations of the place residents are almost nil. The objective of this survey is to analyze the gentilics of the districts of the province of Lima, those that belong to Metropolitan Lima and the Constitutional Province of Callao. For this, the words are listed and studied according to the lexicographic technique. The research concludes with the importance of knowing the gentilics, their meaning, their writing and their spelling variants, features linked to the identity of the locals.